2016
DOI: 10.1038/npp.2016.170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anodal Transcranial Direct Current Stimulation and Serotonergic Enhancement on Memory Performance in Young and Older Adults

Abstract: In the absence of effective therapies for dementia and its precursors, enhancing neuroplasticity by means of non-invasive brain stimulation such as anodal transcranial direct current stimulation (atDCS) might be a promising approach to counteract or delay the onset of cognitive decline, but effect sizes have been moderate so far. Previous reports indicate that increasing serotonin levels may enhance atDCS-induced neuroplasticity. However, evidence for serotonergic modulation of atDCS effects on memory is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…Incremental increases in extracellular serotonin levels, using selective serotonin reuptake inhibitor (SSRI), boost anodal facilitation of MEP and caused ctDCS to have an excitatory effect (Nitsche et al, 2009). Moreover, atDCS of the temporal cortex improved memory formation when serotonergic neurotransmission was enhanced simultaneously (Prehn et al, 2016). Thus, tDCS magnifies the activity of serotonergic system.…”
Section: Neuromodulators and Tdcsmentioning
confidence: 99%
“…Incremental increases in extracellular serotonin levels, using selective serotonin reuptake inhibitor (SSRI), boost anodal facilitation of MEP and caused ctDCS to have an excitatory effect (Nitsche et al, 2009). Moreover, atDCS of the temporal cortex improved memory formation when serotonergic neurotransmission was enhanced simultaneously (Prehn et al, 2016). Thus, tDCS magnifies the activity of serotonergic system.…”
Section: Neuromodulators and Tdcsmentioning
confidence: 99%
“…Moreover, the use of a higher dose might be problematic, because of safety and tolerability reasons in the meaning of increasing the risk of side effects which could in turn negatively affect subject blinding. Given that we have previously found positive effects with the application of 1 mA on OLM (Floel et al, 2012 ; Antonenko et al, 2017 ; Prehn et al, 2017 ), alternative factors, e.g., timing in relation to task, interindividual differences, or a combination, might contribute to null finding.…”
Section: Discussionmentioning
confidence: 74%
“…Electrodes were attached to the scalp using rubber bands. Given that right temporoparietal region is implicated in the acquisition of OLM (Postma et al, 2008 ) and anodal tDCS over this area has been shown to improve performance on a similar version of the task employed in our study (Floel et al, 2012 ; Prehn et al, 2017 ) this site was selected for anodal simulation. Note, that the larger size of the cathode renders the stimulation density functionally ineffective.…”
Section: Methodsmentioning
confidence: 99%
“…The active electrode (anode, 5x7 cm 2 ) was positioned over the right temporoparietal cortex, centered on T6 (according to international EEG 10-20 System) known to be implicated in acquisition of OLM [75]. Moreover, atDCS over this area has been shown to improve performance on a similar version of the task employed in our study [25,76]. The return electrode (cathode, 10×10 cm 2 ) was placed contralateral over the left supraorbital area (see also Fig.…”
Section: Brain Stimulationmentioning
confidence: 92%